Correlation between intensive phase treatment of antituberculosis drugs with nutritional status of patients with tuberculosis in Kupang city - William Lie; Ika Febianti Buntoro; Rahel Rara Woda; Christina Olly Lada (Indonesian Nutrition Association, 2020)
Background: Indonesia is a country with the third highest tuberculosis incident in the world. Nutritional status is very important to patients with tuberculosis, an optimal nutritional status created an optimal immune system. Lack of adequate nutritional intake, prolonged the anti-tuberculosis drug treatment and caused them to get a slower recovery. Therefore, the writer found the need of knowing the relation of intensive phase treatment of anti-tuberculosis drugs with nutritional status of patients with tuberculosis in Kupang City.Objectives: To know the relation between intensive phase treatment of anti tuberculosis drugs with nutritional status of patients with tuberculosis in Kupang City.Methods: This study was an observational analytic study with a nested cohort design conducted by 11 public health centers in Kupang City by taking secondary data from medical records. The sampling technique used consecutive sampling with 84 respondents who met the inclusion and exclusion criteria. The study was analyzed univariately, and bivariately using Mc Nemar.Results: From 84 respondents, before intensive phase tuberculosis treatment 61 respondents (72.6%) had abnormal nutrition status, and 23 respondents (27.4%) had normal nutritional status, while after intensive phase tuberculosis treatment from 84 respondents it was found that 50 respondents (59.5%) had abnormal nutrition status, and 34 respondents (40.5%) had normal nutritional status. The result of the bivariate analysis test shows a significant different in nutritional status before and after tuberculosis treatment with p value = 0.001.Conclusions: There was a significant different in nutritional status before and after tuberculosis treatment indicating that anti-tuberculosis drug treatment can affect the nutritional status of patients with tuberculosis.Cl